Insidious risk of severe Mycobacterium chimaera infection in cardiac surgery patients. - Chand, M; Lamagni, T; Kranzer, K; Hedge, J; Moore, G; Parks, S; Collins, S; Del Ojo Elias, C; Ahmed, N; Brown, T; Smith, E; Hoffman, P; et al. (Oxford University Press, 2016)
Background An urgent UK investigation was launched to assess risk of invasive Mycobacterium chimaera infection in cardiothoracic surgery and a possible association with cardiopulmonary bypass heater-cooler units following alerts in Switzerland and The Netherlands. Methods Parallel investigations were pursued: (1) identification of cardiopulmonary bypass–associated M. chimaera infection through national laboratory and hospital admissions data linkage; (2) cohort study to assess patient risk; (3) microbiological and aerobiological investigations of heater-coolers in situ and under controlled laboratory conditions; and (4) whole-genome sequencing of clinical and environmental isolates. Results Eighteen probable cases of cardiopulmonary bypass–associated M. chimaera infection were identified; all except one occurred in adults. Patients had undergone valve replacement in 11 hospitals between 2007 and 2015, a median of 19 months prior to onset (range, 3 months to 5 years). Risk to patients increased after 2010 from <0.2 to 1.65 per 10 000 person-years in 2013, a 9-fold rise for infections within 2 years of surgery (rate ratio, 9.08 [95% CI, 1.81–87.76]). Endocarditis was the most common presentation (n = 11). To date, 9 patients have died. Investigations identified aerosol release through breaches in heater-cooler tanks. Mycobacterium chimaera and other pathogens were recovered from water and air samples. Phylogenetic analysis found close clustering of strains from probable cases. Conclusions We identified low but escalating risk of severe M. chimaera infection associated with heater-coolers with cases in a quarter of cardiothoracic centers. Our investigations strengthen etiological evidence for the role of heater-coolers in transmission and raise the possibility of an ongoing, international point-source outbreak. Active management of heater-coolers and heightened clinical awareness are imperative given the consequences of infection.